FAKTOR-FAKTOR YANG MEMENGARUHI USAHATANI PADI GOGO (Oryza sativa. L) DI DESA PAKENG KECAMATAN LEMBANG KABUPATEN PINRANG - Sudirman; Irmayani Irmayani; Darmawan (Fakultas Pertanian, 2023)
Rice (Oryza sativa L) is a very important food crop in the world after wheat and corn. Upland rice is a variety of rice cultivation, namely planting rice on dry land. Upland rice is generally planted once a year at the start of the rainy season. The aims of this study were 1) to find out what factors influenced upland rice farming in Pakeng Village, Lembang District, Pinrang Regency. . 2) To find out what factors had a significant effect on upland rice farming in Pakeng Village, Lembang Distric Pinrang Regency. This study uses a quantitative descriptive research method because the implementation includes data, analysis and interpretation of the meaning of the data obtained, the data used in this study are primary and secondary data. There were 75 samples in the study which were then processed using SPSS 21 and analyzed using multiple linear regression analysis technique. From the results of the study it was obtained: that the variables of land area, fertilizer, labor had a positive but not significant effect, while herbicides and technology had a significant effect on upland rice farming in Pakeng Village, Lembang District, Pinrang Regency.